2001
DOI: 10.1007/pl00004064
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the interaction of shock waves with textiles

Abstract: Experimental studies have been performed to investigate the pressure amplification experienced behind a textile when exposed to a shock wave. Three textiles with different masses and air permeabilities were studied. Mach numbers for tests varied between 1.23 and 1.55. The distance between the back wall and the textile was varied between 3 and 15 mm. It was found that in most cases the presence of the textile led to a pressure amplification at the back wall. This amplification was dependent on the textile, Mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
3
7
0
Order By: Relevance
“…Shock tube studies [6] support the field observations. These studies focus on the actual mechanisms that lead to the pressure amplification, which is defined as the ratio of peak pressure on the surface with textile present, to that which would be achieved with shock reflection off a bare surface.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Shock tube studies [6] support the field observations. These studies focus on the actual mechanisms that lead to the pressure amplification, which is defined as the ratio of peak pressure on the surface with textile present, to that which would be achieved with shock reflection off a bare surface.…”
supporting
confidence: 59%
“…For the visualization tests and those with gelatin backing the same textiles were used as in the previous study [6], namely satin, polycotton, and muslin, as shown in Figure 3, and having the properties listed in Table 1. The samples shown were 76 mm wide and the insert, at five times magnification, gives an indication of the structure.…”
Section: Textiles Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…When supported by a rigid wall, the overall stress acting on the wall can be reduced or amplified depending on whether the porous medium is rigid or flexible, respectively. Stress amplification has been reported in experiments with flexible porous materials such as polyurethane foams (Skews 1991;Baer 1992;Levi-Hevroni et al 2002;Seitz & Skews 2006), textiles (Hattingh & Skews 2001) and granular materials when theywere placed immediately adjacent to a supporting wall (Ben-Dor et al 1997; † Email address for correspondence: sorens@bgu.ac.il 508 O. Ram and O. Sadot Britan et al 1997b;.…”
Section: Introductionmentioning
confidence: 99%